A longitudinal study on the relation between parenting and Toddler’s disruptive behavior: what is the role of Toddler’s negative emotionality and physiological stress reactivity? - Huijzer-Engbrenghof, Marijke; van Rijn-van Gelderen, Loes; Spencer, Hannah; Wesarg-Menzel, Christiane; Creasey, Nicole; Lalihatu, Esmee S.; Overbeek, Geertjan (Frontiers in Psychology, 2024)
Harsh and unsupportive parenting is a risk factor for the development of disruptive behavior in children. However, little is known about how children's temperament and stress reactivity influence this relation. In a three-wave longitudinal study, we examined whether the associations between parenting practices (supportive parenting, positive discipline, and harsh discipline) and child disruptive behavior were mediated by child temperament (negative emotionality) and stress reactivity (heart rate reactivity). In 72 families (Mage child = 14.6 months), parents reported on their parenting practices and their children's disruptive behavior and negative emotionality. Children's heart rate reactivity was assessed through a series of stress-inducing tasks. Results from regression-based mediation analyses with bootstrapping showed that negative emotionality and stress reactivity did not mediate the relation between parenting and disruptive behavior. The results overall demonstrate that in a group of children this age, a reinforcing dynamic between parenting, child stress and disruptive behavior is not yet firmly established.